Expanded clay basalt fiber concrete: Solving structural defects caused by water penetration. Issue 1 (1st January 2021) - Chiadighikaobi, Paschal Chimeremeze; Tefera, Bewuket Bekele; Olakunbi, Tarka Rilwan; Vladimir, Jean Paul
Abstract: The objective of this research paper is to analyze the materials which can be suggested for usage to solve the problem of structural defect caused by water absorption through penetration. Each of the concrete types was made in five concrete mix series of 0%, 0.45%, 0.9%, 1.2%, and 1.6% of chopped basalt fiber. Each of the concrete series was shared into two sets where the first set was tested for strength on the day 28 curing period while the second set was soaked in immersed in water at room temperature for additional 96 hours after the day 28 before testing for strength. The compressive strength of the expanded clay concrete cube specimen tested on day 28 curing period showed an increase in strength to 34.71 MPa lesser than the set with immersed in water for additional 96 hours to 37.38 MPa. Similarly, conventional concrete cube specimens at day 28 compressive strength to 29.97 MPa and to 29.97 MPa for conventional concrete after day 28. Expanded clay concrete showed more flexural strength of 2.921 MPa at day 28 and 2.895 MPa for concrete after day 28 with additional 96 hours in water. Similarly, on flexure, conventional concrete specimens showed flexural strength up to 1.917 MPa at day 28 while up to 1.733 MPa after day 28 with additional 96 hours in water. Concrete containing 1.6% basalt fiber gave more strength and improves the concrete capability.